Evaluación de la carne bovina que se expende en el mercado Municipal del cantón Celica, Provincia de Loja - Torres Montalván, Jorge Luis (2014)
This work was executed in the slaughterhouse and Municipal Market City Celica, in which the "Quality assessment of bovine meat sold in the municipal market of Canton Celica province of Loja" for conducting the performed present the following objectives: Contribute to the consumer population and producer of beef in the city of Celica, regarding the evaluation of the safety of the same; Evaluate the production chain of beef from the centers of production to centers of sale; Analyze the beef that is sold in the city of Celica, under the influence of the chain of slaughter during expend the public according to the physical-chemical sensory and microbiological characteristics; Share the results with producers, retailers and consumers based on the results and make a proposal. The method of analysis was: measuring temperature and pH every two hours for 8 consecutive weeks, after the arrival of the meat market and further samples of meat from 100 g was taken, (previously meat different cuts of the same mixed animal and this was collected for microbiological analyzes. descriptive statistical analysis was applied. For the development of this work handling cattle at the farm level was analyzed, livestock producers maintain the extensive system and method of operation, not running pasture management tasks such as fertilization. The dominant grasses are brachiaria and Kikuyu and also are the higher biomass production. Compared to others like the elephant it has lower acceptability due to the degree of palatability, the average production of meat / year is 200kg / ha / year. The animals on arrival are not received in pens to give a previous period of rest for slaughter, directly they are subjected to the process of slaughtering and do not meet basic indicators for managing ante as predip stun to be produce a good bleeding., slaughter activities is done at ground level, without complying with any rules in force. The movement of the pieces of meat to the Municipal Market Celica is done in open trucks and were not received in cold rooms for the process slaughterhall is given, begin the sale as it comes is in muscle. Taken market Ph and meat temperature every 2 hours from the arrival, and the results were averaged microbiological examination concerning the study of bacteria was carried out as: E. coli, coliforms and Enterobacteriaceae have been developed in the meat bovine; taking pH and temperature were performed at three times after slaughtering cattle. To then be analyzed in the Microbiology Laboratory of the Central University of Ecuador. Average results of 8 weeks were of research temperature: 2 H00 22,4ºC, the 4H00 18.76 ° C, 6 H00 17 ° C, pH level was obtained for the same time as the above two H00 6.82, 5.74 to 4H00, 6 H00 5.22. Microbiological values were: two hours enterobacteria dressing 55.5 cfu / g. four hours 254.6 cfu / g and the sixth hour was obtained 561.6 cfu / g, echericha coli at two hours dressing with 24.4 cfu / g, four hours 67.9 cfu / g and the six hours a sample 129.9 cFU / g, coliform with the following results at two hours with 28.0 cFU / g at four hours with 193.0 cFU / g and was obtained six hours a sample was obtained 352.4 cfu / g, in microbiological growth: Enterobacteriaceae bacteria, e. coli and coliform in the first 6 hours are maintained within a range of acceptance for human consumption, but the last time this meat consumption is acquired is not recommended because bacteria multiply geometrically. It is concluded that systems operating the property under consideration are extended, aspect that influences weight gain is low. In the slaughter stun no death that is given to cattle from cardiac arrest, muscle and no meat is consumed in the absence of the maturation process. In microbiological growth: Enterobacteriaceae bacteria, e. coli and coliform in the first 6 hours are maintained within a range of acceptance for human consumption, but the last time this meat consumption is acquired is not recommended because bacteria multiply geometrically.